Concentrated disadvantage, racial disparities, and juvenile institutionalization within the context of attribution theory - Lowery, Patrick G. (Criminal justice studies, 2019)
Prior literature has noted that disparities happen within the juvenile court process across a variety of contexts. However, research exploring this theme often neglects to use attribution theory to understand how external community-based attributions, particularly racialized interactions with real or perceived disadvantages within a community, as well as various internal attributions, and how these considerations shape placement decisions. Using quantitative juvenile court data from one southeastern state in the United States, supplemented with American Community Survey data, this study draws upon attribution theory to explore how internal and external attributions affect the placement decisions of serious and violent juveniles.